Laboratory Studies on Creep Behavior of Grouted Tensioned Rebar in Weak Strata - Anthony (Sam) J. S. Spearing; Aditya Mishra; Naga S. Y. Tirumalaraju; Joseph Hirschi (International Conference on Ground Control in Mining, 2015)
"Primary roof support in underground coal mines in the USA consists mostly of fully grouted passive rebar or grouted (partially or fully) tensioned rebar. Research conducted at two room-and pillar coal mines in the Illinois Basin and one longwall mine in Colorado monitored the performance of these passive and active rock bolts under similar geologic and mining conditions and found no significant initial loads in either passive or active rock bolts (Spearing et al., 2011). Active rock bolts showed significant loss of initial pre-load, although the exact reasons for this were not fully investigated. Subsequent laboratory testing has also shown that in weak rock, resin creep occurs, caused by slippage of the mechanical key between resin column and rock interface. These creep tests were studied in the laboratory in an effort to quantifythis phenomenon.INTRODUCTIONResin-grouted rock bolts are the first and main line of defense to counter roof and rib falls in underground coal mines of the United States. Rock bolts are categorized as active or passive. Active bolts are tensioned during installation whilst no (or limited) tension is applied to passive bolts, which need subsequent strata movement to generate reactive loads. During installation of passive bolts, some reactive pre-load may be generated by a significant up-thrust from the rock bolter boom.The selection of active or passive bolts is critical and is mostly dependent on the conditions and properties of the immediate roof (Unrug, 2009). This decision is frequently made based on personal experience, bias, and most recently cost. Active bolts are generally used in cases of highly laminated roof rock. When active bolts are tensioned, they develop compressive forces between these layers forming a beam, which helps to stabilize weak individual layers thereby increasing frictional forces between layers and decreasing effects of horizontal stresses. The fully grouted tensioned rebar system is high in stiffness as compared to mechanical bolts and provides higher surface area of contact along the length of the bolt due to the grout, which permits it to develop a strong anchorage mechanism."